COORDINATION AND COMBINATION OF COLORS IN PAINTING (WITH REFERENCE TO PREHISTORIC PERIOD AND MODERN PERIOD): चित्रकला में रंगों का समन्वय एवं संयोजन (प्रागैतिहासिक काल एवं आधुनिक काल के संदर्भ में) - Shere, Pramila (International Journal of Research -GRANTHAALAYAH, 2014)
The art of prehistoric India is easily introduced to the art of prehistoric India by studying the motifs of textiles, stone paintings, clay characters, creeping insects, animals, birds, humans etc. available from different regions of India. Like today, Adi Man was also a beauty doctor. Due to this aesthetic love, he tended to give tangible form to his abstract feelings. We find evidence of this in the art materials available from the excavations of Mohenjodaro and Hadappa. It is known from a verse in the ancient mantra samhita of the Rig Veda that at that time there was a practice of painting on leather. In some of the mantras of the Rig Veda, there is mention of inscriptions of goddesses on the boards of the Yajnashalas. The art of culture flourished and preserved by Emperor Ashoka is seen even today. Buddhism has a special reputation in the production of paintings. The calligraphy of the lines in the paintings of the tiger and Ajanta and the various conventions of the use of colors express the development of the painting of this era. The actual form of Gupta art is seen in the paintings of Ajanta, Ellora and tiger caves. Graffiti has an important place in the history of Indian painting. The frescoes are seen in the caves of Bhimbetka, Jogimara, Tiger, Ajanta Badami, Sittanvasal, Ellora, Elephanta. South India has also been a pioneer in the rise of painting. In the history of Indian painting, Rajput style has its own distinctness and its own independent existence. After the establishment of the Mughal period in India, a new direction in the field of painting came to light. Himachal Pradesh has been the land of construction of hill pictures - Jammu, Tehri, Garhwal, Kallu, Chamba, Basauli, Kangra etc. भारत के विभिन्न क्षेत्रों से उपलब्ध वस्त्रों, पाशाणचित्रों, मृत्तिका पात्रों, लाल-पीले रंगों में चित्रित रेंगते हुए कीड़ों, पशुओं, पक्षियों मनुष्यों आदि की आकृति का अध्ययन करके प्रागैतिहासिक भारत के कलाप्रेम का सहज ही मंें परिचय मिल जाता है। आज की भाँति आदि मानव भी सौन्दर्योपासक था। इसी सौन्दर्यप्रेम के कारण वह अपने अमूर्त भावों को मूर्त रुप देने की ओर प्रवृत्त हुआ। इसके प्रमाण हमें मोहनजोदड़ो तथा हडप्पा की खुदाईयों से उपलब्ध कला सामग्री में देखने को मिलते है। ऋगवेद की प्राचीनतम मंत्र संहिता की एक ऋचा से ज्ञात होता है कि उस समय चमड़े पर चित्र अंकित करने का प्रचलन था। ऋगवेद के कुछ मंत्रों में यज्ञषालाओं की चैखटों पर द्वार देवियों के चित्र अंकित किये जाने का उल्लेख मिलता है। सम्राट अषोक द्वारा पल्लवित एवं संरक्षित कला की थाती आज भी देखने को मिलती है। पटचित्रों के निर्माण में बौध्दकला की विशेष ख्याति रही है। बाघ और अजंता के चित्रों में रेखाओं का सुलेखन और रंगों के प्रयोग की विभिन्न परिपाटियाँ इस युग के चित्रांकन का विकास व्यक्त करती है। अजंता, एलोरा और बाघ की गुफाओं की चित्रकारी में गुप्तकालीन कला का वास्तविक रुप देखने को मिलता है। भारतीय चित्रकला के इतिहास में भित्तीचित्रों का महत्वपूर्ण स्थान है। भित्तिचित्र भीमबेटका, जोगीमारा, बाघ, अजन्ता बादामी, सित्तनवासल, ऐलोरा, ऐलीफेंटा की गुफाओं में देखने को मिलते है। चित्रकला के उत्थान में दक्षिण भारत भी अग्रणी रहा है। भारतीय चित्रकला के इतिहास में राजपूत षैली की अपनी विशिष्टता और अपना स्वतंत्र अस्तित्व है। भारत में मुगल काल की स्थापना के बाद चित्रकला के क्षेत्र में एक नयी दिषा प्रकाष में आयी। पहाड़ी चित्र षैलियों की निर्माण भूमि हिमाचल रहा है-जम्मू, टिहरी, गढवाल, कल्लू, चम्बा, बसौली, कांगड़ा आदि इसके क्षेत्र रहे है।